2020
DOI: 10.1371/journal.pntd.0008365
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of degradable polyanhydride particles in Aedes aegypti tissues

Abstract: Insecticide resistance poses a significant threat to the control of arthropods that transmit disease agents. Nanoparticle carriers offer exciting opportunities to expand the armamentarium of insecticides available for public health and other pests. Most chemical insecticides are delivered by contact or feeding, and from there must penetrate various biological membranes to reach target organs and kill the pest organism. Nanoparticles have been shown to improve bioactive compound navigation of such barriers in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Interestingly, mosquitoes feeding on sugar alone were significantly more susceptible to the effects of permethrin, although sugar‐only‐fed mosquitoes weighed the same as sugar‐water‐fed, suggesting mosquitoes did in fact feed on the sugar. This is also supported by previous studies that demonstrated mosquitoes can feed on dry sugar 17,18 . These results suggest that insecticide tolerance is not primarily mediated by carbohydrate reserves.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, mosquitoes feeding on sugar alone were significantly more susceptible to the effects of permethrin, although sugar‐only‐fed mosquitoes weighed the same as sugar‐water‐fed, suggesting mosquitoes did in fact feed on the sugar. This is also supported by previous studies that demonstrated mosquitoes can feed on dry sugar 17,18 . These results suggest that insecticide tolerance is not primarily mediated by carbohydrate reserves.…”
Section: Discussionsupporting
confidence: 88%
“…This is also supported by previous studies that demonstrated mosquitoes can feed on dry sugar. 17,18 These results suggest that insecticide tolerance is not primarily mediated by carbohydrate reserves. Water-only-fed mosquitoes weighed the same as starved, which may reflect the lack of feeding stimulus or carbohydrate storage provided by the sugar.…”
Section: Discussionmentioning
confidence: 80%
“…Fluorescent confocal imaging appeared to show caveolae-mediated endocytosis is a primary pathway for lipoplexes, but the other two endocytic pathways also had some role in uptake. A similar study [ 141 ] in mosquitoes ( A. aegypti ) found caveolae-mediated endocytosis is essential for nanoparticle (anhydride) internalization into epithelial cells. This is especially true for smaller particles (<100 nm) but could also allow larger particles such as lipoplexes which can easily exceed that size.…”
Section: Importance Of Understanding Dsrna Uptakementioning
confidence: 88%
“…For example, synthetic hydrogels are applied in agriculture for nutrient or pesticide release, for absorption and sustained release of water, particularly in dryland farming in soil-less agriculture, or hygiene products such as diapers [20,21]. Synthetic hydrogels are already used in pest management, mainly for the release of chemical insecticides through beads as baits or for controlled release in water or microencapsulation for spraying and release of active substances [22,23]. Examples are PAM or silica and talc-based gels [24,25] inserted in a polyethylene container to slowly release an insect growth regulator or other synthetic insecticides in pest and vector control [26,27].…”
Section: Introductionmentioning
confidence: 99%